2020
DOI: 10.3390/nu12123661
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Anorexia Dynamically Dysregulates the Glutamatergic Synapse in the Nucleus Accumbens of Female Adolescent Rats

Abstract: Intense physical activity and dieting are core symptoms of anorexia nervosa (AN). Their combination evolves into compulsivity, leading the patient into an out-of-control spiral. AN patients exhibit an altered activation of nucleus accumbens (NAc), revealing a dysfunctional mesocorticolimbic reward circuitry in AN. Since evidence exists that a dysregulation of the glutamate system in the NAc influences reward and taking advantage of the activity-based anorexia (ABA) rat model, which closely mimics the hallmarks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…And those patients do not adequately respond to homeostatic body signals such as appetite regulating peptides that should trigger weight restoration [ 46 ]. The central aspects related to AN etiopathogenesis (for a review see, Skowron et al 2020) [ 11 ] are beyond the scope of this article; however, it should be noted that research using animal models, including the ABA model, has contributed immensely to the understanding of potential brain mechanisms that many underlie the causes and consequences of aberrant eating behaviors [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…And those patients do not adequately respond to homeostatic body signals such as appetite regulating peptides that should trigger weight restoration [ 46 ]. The central aspects related to AN etiopathogenesis (for a review see, Skowron et al 2020) [ 11 ] are beyond the scope of this article; however, it should be noted that research using animal models, including the ABA model, has contributed immensely to the understanding of potential brain mechanisms that many underlie the causes and consequences of aberrant eating behaviors [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, since mGluR5 expression is not restricted to astrocytes but also found in neurons [ 49 ], it remains to be clarified whether these observations are specific to astrocytes although several hints suggest that glutamatergic gliotransmission plays a role in food intake control. Additionally, changes in glutamatergic signaling in an experimental ABA animal model were found: The expression of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunits GluA1, which mediates together with other subunits synaptic transmission, is enhanced in the nucleus accumbens potentially due to a disturbed mesocorticolimbic reward circuitry [ 50 ]. A recently published study using the same model showed that the increase in running wheel behavior correlates negatively with GLT-1 levels in the hippocampus indicating GLT-1 enhancement may counteract the severity of AN [ 51 ].…”
Section: Disturbed Gliotransmission As a Regulator Of Feeding Behaviormentioning
confidence: 99%
“…Evidence exists, in both AN patients and animal models, that maladaptive reorganization of the mesocorticolimbic structures may represent the neurobiological underpinning of the motivational mechanisms underlying AN phenotype (Foldi et al, 2017; Frank et al, 2018; Ho et al, 2016). In this scenario, it is possible to hypothesize that dysfunctions of glutamate homeostasis, which has been proposed as a signal of altered processing of food reward (Mottarlini et al, 2020; Murray & Holton, 2021; Ohrmann et al, 2004), may contribute to the anorexic phenotype. This possibility is supported by a recent pilot study at 7 Tesla, in which Godlewska and coworkers found that glutamate levels were diminished in the occipital cortex of AN patients, anterior cingulate cortex, and putamen, whereas the ratio of glutamine to glutamate was significantly increased, suggesting a hypoglutamatergic transmission in AN (Godlewska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%